Effect of dry-wet cycles on dynamic mechanic and microstructure of cemented broken mudstone. (28th November 2022) - Yi, Qingyu; Pu, Hai; Preuße, Axel; Bian, Zhengfu; Wu, Jiangyu
Highlights: Effect of dry-wet cycles on strength of cemented broken mudstone (CBM). Prediction model of dynamic compression strength (DCS) based on ultrasonic detection. Effect of dry-wet cycles on microstructure and hydration of CBM. Influence mechanism of strain rate and dry-wet cycles on CBM. Abstract: The secondary utilization of abandoned mine is usually accompanied by water erosion, cyclic impact, and induced earthquake, which induces a great engineering challenge for the mudstone stratum reconstruction. Consequently, this paper carried out ultrasonic detection, split Hopkinson pressure bar (SHPB) impact, thermogravimetry, and mercury intrusion porosimetry tests to investigate the dynamic performance and microstructure of reinforcing mudstone under water erosion. The results show that the dynamic compression strength (DCS) and strain-rate enhancement effect of cemented broken mudstone (CBM) firstly increase and then decrease with the increase of dry-wet cycles, the maximum growth is 15.38% for CBM in 3 dry-wet cycles while the maximum drop is 19.63% for that in 9 dry-wet cycles. The dry-wet cycles mainly affect the DCS by changing the elastic limit strength, and promote the carbonization of Ca(OH)2 to produce up to 9.365% CaCO3 during the cemented matrix's hydration. In the late dry-wet stage, the deterioration of internal mudstone particles induces pore cracks and causes up to 19.63% decrease in DCS. This study reveals the evolution law of dynamic mechanical properties of CBM under water erosion, and provides experimental reference for the reconstruction of abandoned mine.